Thirty-five years of floristic collections in southern Tuscany (Italy) - Federico Selvi; Stefano Martellos; Matteo Conti (Biodiversity Data Journal)
Floristic knowledge and georeferenced information about vascular plant species distribution in southern Tuscany (Italy) are still poor for supporting effective biodiversity conservation efforts.A dataset of georeferenced floristic collections from Southern Tuscany, which was developed by the first author between 1989 and 2024, is provided and briefly commented on. The dataset includes data for 4535 herbarium specimens, mostly unpublished, currently preserved in the Herbarium Centrale Italicum at the Natural History Museum of Florence (FI). The specimens belong to 1766 species and subspecies in 122 families of vascular plants. Each record is associated with a Unique Identifier (UID) and information on the collection locality, date, collector(s), and geographical coordinates (WGS84 geodetic datum). Many specimens were collected in areas that were poorly investigated, documenting new sites for several uncommon or phytogeographically relevant taxa. The dataset includes two specimens of Euphorbia meuselii Geltman, a forest herb endemic to Southern Italy and new to the flora of Tuscany. Overall, this dataset allows a relevant advancement in the floristic knowledge of central Italy.